2018
DOI: 10.1111/cob.12292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of spin within abstracts in obesity randomized clinical trials: A cross‐sectional review

Abstract: This is a cross-sectional analysis of spin in randomized controlled trial (RCT) abstracts published in top-ranked obesity and general medicine journals. The top seven obesity and four general medicine journals were searched from 1 January 2016 to 31 December 2017. To be included in this study, a trial must be an RCT with non-significant primary endpoint (P > 0.05), exclusively randomize subjects with overweight or obesity or have a primary endpoint of weight loss. These studies were analysed by two reviewers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 15 publications
7
50
2
Order By: Relevance
“…Our results agreed with other studies in the medical literature that investigated spin strategies and misrepresentation of RCT results with various methodologies [4,5,[51][52][53][54]. Austin et al [5] reported some form of spin to exist in 47% of the included RCT abstracts while Cooper et al [53] reported spin to be as high as 70% of the included articles.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results agreed with other studies in the medical literature that investigated spin strategies and misrepresentation of RCT results with various methodologies [4,5,[51][52][53][54]. Austin et al [5] reported some form of spin to exist in 47% of the included RCT abstracts while Cooper et al [53] reported spin to be as high as 70% of the included articles.…”
Section: Discussionsupporting
confidence: 90%
“…Our results agreed with other studies in the medical literature that investigated spin strategies and misrepresentation of RCT results with various methodologies [4,5,[51][52][53][54]. Austin et al [5] reported some form of spin to exist in 47% of the included RCT abstracts while Cooper et al [53] reported spin to be as high as 70% of the included articles. Interestingly, Pitkin et al [8] compared data reported in the abstract of a random sample of RCTs published in 6 major medical journals to the data presented in the full-text manuscripts and found that inconsistencies at variable levels (18%-68%) existed between data reported in the abstract compared to the full text.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Two investigators (SJ and HW) screened all studies for eligibility in an independent, blinded fashion which is consistent with our previous investigations 12–14. We used Rayyan, an online systematic review application, to screen PubMed records for eligibility with the blinding feature turned on.…”
Section: Methodsmentioning
confidence: 93%
“…This is important because it goes against a commonly expressed view that industry funding may have a direct or indirect effect on an investigator to explicitly describe nonsignificant results. 19 , 20 , 21 , 22 However, a 2009 report 23 highlighted high rates of underreporting of financial conflicts of interest by investigators. It is possible that researchers who are prone to spin may intentionally or unintentionally underreport their financial relationships.…”
Section: Discussionmentioning
confidence: 99%